Beyond habitat boundaries: Organic matter cycling requires a system‐wide approach for accurate blue carbon accounting. Issue Volume 67:Issue S2(2022) (26th March 2022) - Krause, Johannes Renke; Hinojosa‐Corona, Alejandro; Gray, Andrew B.; Herguera, Juan Carlos; McDonnell, Julianna; Schaefer, Michael V.; Ying, Samantha C.; Watson, Elizabeth Burke
Abstract: As coastal ecosystems become widely recognized for their capacity to sequester carbon (blue carbon), standard accounting methodologies for the generation of carbon credits are being developed. To ensure the applicability of these standards across blue carbon ecosystems, we investigated organic carbon provenance and burial in salt marshes and seagrass meadows of an arid, upwelling‐dominated Eastern Pacific lagoon. We found low carbon density in benthic sediments of Bahía de San Quintín (5.9 ± 0.5 mg C cm −3 ), only marginally higher in Zostera marina beds (6.9 ± 0.5 mg C cm −3 ), likely due to remineralization and hydrodynamically driven export of seagrass material, resulting in low carbon burial rates (4.5 ± 2.5 g C m −2 yr −1 ). Sediment organic carbon is mainly controlled by the fraction of fine sediment and its source is largely allochthonous, although sources differ spatially. Salt marshes at San Quintín derive 40% of their organic matter from autochthonous material and exhibit higher carbon burial rates (up to 414.7 ± 28.6 g C m −2 yr −1 ) and sediment carbon densities (32.0 ± 0.7 mg C cm −3 ) compared to benthic sediments. This study emphasizes the connectivity of blue carbon habitats with marsh plant detritus supplementing benthic carbon burial and incorporation of detrital eelgrass in marsh sediments. Our findings highlight the importance of allochthonous organic matter for carbon sequestration in blue carbon habitats, suggesting standard accounting practices that deduct allochthonous organic matter would miss the full potential for carbon burial.